The Causal Link between FDI and Remittances in Kosovo, Switzerland, and Denmark - Kida Nakije (Comparative Economic Research. Central and Eastern Europe, 2021)
The pursuit of money and capital is a relentless endeavor of every economy. FDI is considered the engine of economic growth, while are remittances the increasingly the catalyst of the population's welfare. The purpose of the study is to analyze the answer about the relationship between remittances and FDI inflows in Kosovo, Switzerland and Denmark. Secondary data obtained from the World Development Indicators were, analyzed with the Ordinary Least Squares model and Granger Causality and processed with SPSS 21 technique. Measuring the correlation between variables, Foreign Direct Investment, GDP per capita growth, net migration, remittances, Gross Fixed Capital Formation, household consumption, and population number, give reliable results. Using remittances as a dependent variable, the first hypothesis has been partially confirmed, the most statistically significant and positive determinants that increase remittances are population, unemployment and migration and not other determinants. The regression results are unsatisfactory for the second hypothesis dependent variables Foreign Direct Investment the determinants are positive but not statistically significant, confirming that there are other factors that impact the increase of FDI inflows. The correlation matrix shows a high correlation between the variables. The Granger Causality model, through the Wald test, represents the cause. FDI does not cause remittances, but remittances cause FDI. A limitation of the study is the heterogeneity of the data and the countries in the sample. The results of the study will be of interest to government institutions in Kosovo to improve the business environment so that the country will become attractive to foreign investors who will bring capital and employment growth.
Keywords: F21; F33; E2; F24; R15; 330; FDI; remittances; panel data; OLS; Granger causality